(untitled) (Journal of Asian Development Studies, 2019)
This study attempts to assess the important determinants of innovation in case of fan industry of Gujrat, Pakistan. It is a sectoral analysis to empirically identify the role of different internal and external characteristics of innovation in enhancing the financial performance of firms. Sample of the study comprises of 100 firms (10 large, 60 medium and 30 small firms). With the tool of questionnaire, empirical analysis is carried through the descriptive analysis. The estimated results indicate that most of the small and medium firms are not paying much attention to innovation due to competitive markets, expenditures on innovation or low demand of their products. On the basis of the findings of the study it can be suggested that the investment on innovation can pay back in improving the productive capacity of these firms.